Impact of 'high-profile' public reporting on utilization and quality of maternity care in England: a difference-in-difference analysis. (April 2015) - Laverty, Anthony A; Laudicella, Mauro; Smith, Peter C; Millett, Christopher
Objectives: To evaluate the impact of 'high-profile' (with extensive media coverage) public reporting versus public reporting without 'high profile' coverage on utilization and perceived quality of maternity services in England's National Health Service. Methods: Analysis of national hospital administrative data using difference-in-difference models with propensity score matching, and of two maternity surveys from 2007 and 2010. Outcomes were counts of women admitted for delivery of a baby and the percentage of women rating their care positively in 2007 and 2010. Results: Hospitals highly publicized as providing the best maternity care in England had fewer admissions annually and lower occupancy rates than the national comparison group (63.0% vs. 77.3%; p = 0.09). There was no statistically significant change in overall maternity admissions in the best hospitals (+2.2%, p = 0.40 at six months), or the worst hospitals (−2.8%, p = 0.49 at six months) during any period in the 36 months after public reporting relative to their matched comparison groups. Survey analyses found that compared to the national comparison group of hospitals without 'high profile' media coverage, the worst rated hospitals experienced greater improvements in perceived quality after public reporting but these findings were not maintained in the analysis of matched hospitals. Conclusions: 'High-profile' public reporting of maternity care in England was not associated with changes in the use of maternity services or improvements in patient-reported quality. These findings provide further evidence that public reporting is unlikely to drive major improvements in health system performance through the mechanism of patient choice.